Performance of Strength Hollow Core Wall Panel in the Precast Concrete System - Aziz, Muhammad Izzuddin; Abdul Ghani, Abdul Halim (Recent Trends in Civil Engineering and Built Environment, 2024)
In order to increase the construction industry's productivity, the Industrialized Building System (IBS) has been put in place. Hollow Core Wall Panel (HCWP) is one of the IBS components in the precast concrete system. Due to this case, the strength of HCWP is important to guarantee the performance of IBS. Therefore, this study was about to determine the optimum strength of concrete between HCWP and Normal Brick Wall (NBW) cast in-situ and also to investigate surface hardness between HCWP and NBW. The specimen test would be collected from IBS plant at Acotec Sdn. Bhd. in Bandar Tenggara, Johor where the sample specimen size dimension collected is 300 mm x 300 mm x 100 mm. The laboratory testing would be conducted after the sample was collected. The HCWP will be evaluated using a compressive strength test to determine the strength of the HCWP. Then, the rebound hammer test which is a non-destructive concrete testing procedure that provides a quick and easy assessment of the concrete's compressive strength also would be conducted. From the analysis that have been done, HCWP is higher than NBW for the compressive strength test and rebound hammer test.